Assessment of Mangrove Distribution, Carbon Stock, and Carbon Sequestration toward Sustainable Coastal Management in Northern Coastal of Subang Regency, Indonesia - Santoso, Nyoto; Asy’Ari, Rahmat; Ulfa, Aulia; Rachmatullah, Adam; Octovianus; Ramadhan, Yusuf (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2026)
Mangrove ecosystems play a crucial role in climate change mitigation through carbon sequestration; however, increasing anthropogenic pressures threaten their function as carbon sinks. Along the northern coast of Subang, Indonesia, information on mangrove carbon stocks remains limited despite its importance for sustainable coastal management. This study assesses mangrove distribution and estimates carbon stocks and CO₂ sequestration potential using Sentinel-2 MultiSpectral Instrument (MSI) remote sensing data. The research was conducted over a period of 5 months, from the midle of June to November 2025. The results show that mangrove density averaged 8,067 ± 5,332 trees ha⁻¹, dominated by Avicennia marina (69%). Estimated carbon stocks reached 183.73 ± 97.04 Mg C ha⁻¹, comprising 130.11 ± 70.36 Mg C ha⁻¹ of aboveground carbon and 53.62 ± 26.95 Mg C ha⁻¹ of belowground carbon. Across 2,684 ha, total carbon storage was estimated at 268,577 Mg C, equivalent to a CO₂ sequestration potential of 984,782 Mg CO₂e. The Support Vector Machine (SVM) Linear model achieved the highest prediction accuracy (R² = 0.86; RMSE = 0.07; MAE = 0.06). These findings highlight the significant contribution of Subang’s mangroves to climate change mitigation and provide essential data to support sustainable coastal management and Indonesia’s FOLU Net Sink 2030 target.